1995
DOI: 10.1518/001872095779049291
|View full text |Cite
|
Sign up to set email alerts
|

Vigilance Latencies to Aircraft Detection among NORAD Surveillance Operators

Abstract: A function of North American Aerospace Defence (NORAD) in North Bay, Ontario, is to identify all aircraft entering Canadian airspace. The first step in performing this task is to detect visually the presence of aircraft from either radar or transponder information presented on display consoles. This challenging, real-world vigilance task was used to investigate factors affecting detection latencies. The experiment revealed that performance varied as a function of geographic area of coverage, the midnight shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 21 publications
2
23
1
Order By: Relevance
“…However, this is contrary to a number of vigilance studies that found a steady vigilance decrement for both novice personnel and experienced personnel (Baker, 1962;Mackworth, 1970;Pigeau et al, 1995;Schmidke, 1976). In these previous studies, both novices and experts were employed to perform the task used in the relevant study.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…However, this is contrary to a number of vigilance studies that found a steady vigilance decrement for both novice personnel and experienced personnel (Baker, 1962;Mackworth, 1970;Pigeau et al, 1995;Schmidke, 1976). In these previous studies, both novices and experts were employed to perform the task used in the relevant study.…”
Section: Discussioncontrasting
confidence: 57%
“…Closer examination of the studies with complex tasks referred to above, indicates that a number used student samples despite using tasks or simulations that were similar to those encountered in the real world (e.g. Hollenbeck et al, 1995;Molloy and Parasuraman, 1996;Pigeau et al, 1995). The current research found a distinct difference in the vigilance dynamics between participants (novices and generalists) with no or less experience, training, and exposure to the type of surveillance task performed in the study, and specialists with more experience, training, and exposure to this type of task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vast body of research has shown that the effects of fatigue include decreased vigilance, adverse mood changes, perceptual and cognitive 2 decrements (Krueger, 1990;Belenky, Wesensten, Thorne, Thomas, Sing, Redmond, et al, 2003;Van Dongen, Maislin, Mullington, & Dinges, 2003), impaired judgment, and increased risk taking (Killgore, Balkin, & Wesensten, 2006), and even decreased marksmanship (Tharion, Shukitt-Hale, & Lieberman, 2003;McLellan, Kamimori, Bell, Smith, Johnson, & Belenky, 2005). Contrary to popular opinion in the military, research has shown that motivation can only partially compensate for the adverse effects of sleep deprivation (Pigeau, Angus, & O'Neil, 1995).…”
Section: A Statement Of the Problemmentioning
confidence: 92%
“…A vast body of research has shown that the effects of fatigue include decreased vigilance, adverse mood changes, perceptual and cognitive decrements (Krueger, 1990;Belenky, Wesensten, Thorne, Thomas, Sing, Redmond, et al, 2003;Van Dongen, Maislin, Mullington, and Dinges, 2003), impaired judgment and increased risk taking (Killgore, Balkin, & Wesensten, 2006), and even decreased marksmanship (Tharion, Shukitt-Hale, & Lieberman, 2003;McLellan, Kamimori, Bell, 2 Smith, Johnson, and Belenky, 2005). Contrary to popular opinion in the military, research has shown that motivation can only partially compensate for the adverse effects of sleep deprivation (Pigeau, Angus, & O'Neil, 1995). Of particular relevance to military training, the ability of individuals to learn and retain information is reduced by sleep deprivation (literature summarized in Miller et al, 2008).…”
Section: Executive Summarymentioning
confidence: 99%